Prior Antithrombotic Therapy Is Associated With Cerebral Microbleeds in Ischemic Stroke Patients With Atrial Fibrillation and/or Rheumatic Heart Disease - Cheng, Yajun; Liu, Junfeng; Zhang, Shuting; Li, Jie; Wei, Chenchen; Wang, Deren; Lin, Jing; Wang, Yanan; Wu, Bo; Zhang, Shihong; Liu, Ming (Frontiers in Neurology, 2019)
Background and purpose: Cerebral microbleeds (CMBs) could contribute to an increased risk of intracerebral hemorrhage in patients with antithrombotic therapy (antiplatelets or anticoagulants). Antithrombotic agents are commonly prescribed to the patients with atrial fibrillation (AF) and/or rheumatic heart disease (RHD) for preventing ischemic stroke. However, the impact of antithrombotic therapy on CMBs remained controversial. We aimed to explore the association between the prevalence of CMBs and prior antithrombotic therapy in ischemic stroke patients with AF and/or RHD. Materials and Methods: Ischemic stroke patients with AF and/or RHD within 7 days of onset from two hospitals were enrolled. Clinical information, prior use of antiplatelets or anticoagulation, presence and location of CMBs on susceptibility weighted imaging were recorded. We investigated the association of antithrombotic use with the presence or location of CMBs using multivariable logistic regression. Results: A total of 160 patients (68 males; median age, 71 years) were included. CMBs were observed in 90 (56.3%) patients, of whom 37 were with strictly lobar CMBs and 53 were with deep or infratentorial CMBs. There was a significant difference in antiplatelet use between patients with and without CMBs (33.3 vs. 11.4%, P = 0.001), but not found in anticoagulants. Prior use of antiplatelets was independently associated with the presence of CMBs (OR 3.075, 95% CI 1.175–8.045, P = 0.022) and especially strictly lobar CMBs (OR 2.635, 95% CI 1.050–6.612, P = 0.039) in multivariate analysis. Conclusions: The present study suggests that CMBs are common in ischemic stroke patients with AF and/or RHD and prior antiplatelet use may relate to the presence of CMBs predominantly in the strictly lobar region. Whether anticoagulants could cause CMBs need to be determined in future longitudinal studies.